Monitoring and Evaluation Function of BPKN RI regarding Consumer Protection Issue in Housing Sector - Celline David; Keizahra Wardhani; Salsabila Putri; Salwani Isnaini; Ana Sabhana Azmy (Universitas Warmadewa, 2024)
The National Consumer Protection Agency of the Republic of Indonesia (BPKN RI) is a bureaucratic body derived from the Ministry of Trade that focuses on handling consumer problems in Indonesia. The paper further examines what makes the housing sector have a high level of complaints at BPKN RI, what types of complaints are filed by consumers and how the form of monitoring and evaluation functions within the scope of BPKN RI in solving problems given by BPKN RI to consumers. This research uses a qualitative method by conducting direct interviews with staff of the Advocacy Division of BPKN RI. The findings obtained are that the monitoring and evaluation of BPKN RI is quite optimal, especially for problems in the housing sector. The number of incoming cases had shown a high number due to the pandemic situation. BPKN RI's evaluation function runs quite well with the achievement of BPKN RI's recommendations being able to become the main basis for the formation of PUPR Ministerial Regulations to protect consumer rights in Indonesia.